Implementasi Kurikulum dalam Pembelajaran Matematika di SD Al Ihsan Yapis Kotaraja - Alifia Nida Safira Meidiah; Ludya Fatmawati (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
This study aims to describe the implementation of the curriculum in mathematics learning at Al Ihsan Yapis Kotaraja Elementary School in the context of the Merdeka Curriculum. The focus of the study includes learning planning, learning implementation, the use of media and learning resources, the role of teachers and schools, and learning evaluation. The research uses a qualitative descriptive approach with data collection techniques through questionnaires, interviews, observations, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing using triangulation techniques to ensure data validity. The results show that the implementation of the curriculum in mathematics learning has been quite effective. Teachers apply student-centered learning through differentiated learning and various learning strategies, such as lectures, discussions, and deep learning approaches. The most widely used media and learning resources are printed books and the internet. Teachers and schools play an important role in creating active learning and supporting the implementation of the Merdeka Curriculum. However, learning evaluation is still dominated by written tests, so it does not fully reflect authentic assessment in accordance with learning objectives. Therefore, improvements are needed in the application of authentic assessment and the integration of learning objectives, learning strategies, and assessment techniques so that curriculum implementation can run more optimally.